EVALUASI CEMARAN BAKTERI PADA SUSU DI TINGKAT PETERNAK, LOPER, DAN KUD DI KECAMATAN GETASAN KABUPATEN SEMARANG - Any Widiyastuti; Dian Wahyu Harjanti; Bhakti Etza Setiani (MEDIAGRO, 2018)
This research was conducted to evaluate the bacterial contamination in fresh milk from farmers, milk collectors, and dairy cooperative (KUD) in Getasan Subdistrict, Semarang Regency. The evaluation of bacterial contamination has been observed by the number of bacteria, milk distribution time, reductation test, alcohol test and pH test of fresh milk samples which had been taken from 30 farmers, 30 milk collectors and 4 dairy cooperatives in Getasan Subdistrict. The result showed that in the farmers, there is 1 positive alcohol test from 30 samples, pH 6, reductation time of 7 hours, and has total bacteria 3.01 × 105 cfu / ml milk. The alcohol test of the milk from collectors also show 1 positive result from 30 samples with pH 6, reduction time of 6 hours and has total bacteria 6.17 × 105 cfu / ml milk. While in alcohol test of dairy cooperative shows 2 positive result, from 4 samples with pH 6, reductation time of 5 hours and has total bacteria 1.38 × 106 cfu / ml milk. The duration of milk distribution from farmer to KUD were 111 minutes. Thus, it is concluded that microbiological quality of milk in farmers and milk collectors level is good because it is below the maximum limit of total bacteria according to Indonesian Standart, but the amount of bacteria milk contamination in dairy cooperative is high due to the duration of distribution (111 minutes) without cooling.Keywords: bacterial count, milk quality, milk safety, distribution time